Corrosion analysis of decorative microporous chromium plating systems in concentrated aqueous electrolytes. (September 2018) - Langer, C.; Wendland, W.; Honold, K.; Schmidt, L.; Gutmann, J.S.; Dornbusch, M.
Abstract: The corrosion behavior of microporous chromium plating systems in concentrated aqueous electrolytes was studied to describe the so-called Russian-mud corrosion of microporous chromium plating systems from decorative car parts. Corrosive stressed chromium plating systems from Russia were analyzed with scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDX) to characterize the specific corrosion mechanism. The electrochemical corrosion behavior was evaluated by potentiodynamic polarization curves, zero resistance ammetry and electrochemical impedance spectroscopy (EIS). The obtained results show two different corrosion mechanisms, dissolving of the chromium plating and undercutting of the chromium plating at specific conditions. Highlights: Russian-mud corrosion on microporous chromium platings system was clarified. The critical de-icing salt composition of each corrosion mechanism was identified. The effect of dearation and acidification of de-icing electrolytes was explained.